Pengembangan SDM Dosen Untuk Meningkatkan Kemampuan Digital Di Era Society 5.0: Studi Kasus di STIT AL IHSAN BALEENDAH - Yusuf, Ilham Agustian Widia; Farihin, Ahmad; Budianto, Cepi; Zulfa, Fitria; Safitri, Lusi (International Conference on Islamic Studies, 2022)
Lecturer Human Resource Development is one of the strategies used in STIT Al Ihsan Baleendah to create lecturers who have good quality, capacity, and capability to apply their academic intellectual abilities, especially digital skills in the learning system process to answer the needs and challenges of dynamic students in the era of society 5.0. STIT Al Ihsan Baleendah is a private high school based on Islamic boarding schools, In the implementation of human resource development for lecturers, there are still several obstacles, one of which is the availability of facilities and infrastructure in the field of technology. The purpose of this study was to determine the development of human resources for lecturers and the performance of STIT Al Ihsan Baleendah lecturers, especially in digital skills in the era of society 5.0. This study uses a descriptive research method with a qualitative approach. This research resulted in the conclusion that the development of human resources for STIT Al Ihsan Baleendah Lecturers using off the job method was carried out by involving lecturers to take part in training and coaching, both formal and non-formal to improve their digital skills.